Nascent rice husk as an adsorbent for removing cationic dyes from textile wastewater - Quansah, Jude Ofei; Hlaing, Thandar; Lyonga, Fritz Ndumbe; Kyi, Phyo Phyo; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Applied Sciences (Switzerland), 2020)
We assessed the applicability of rice husk (RH) to remove cationic dyes, i.e., methylene blue (MB) and crystal violet (CV), from water. RH thermally treated at 75 °C showed a higher adsorption capacity than that at high temperatures (300-700 °C). For a suitable CV-adsorption model, a pseudo-first-order model for MB adsorption was followed by the kinetics adsorption process; however, a pseudo-second-order model was then suggested. In the qt versus t1/2 plot, the MB line passed through the origin, but that of CV did not. The Langmuir isotherm model was better than the Freundlich model for both dye adsorptions; furthermore, the adsorption capacity for MB and CV was 24.48 mg/g and 25.46 mg/g, respectively. Thermodynamically, the adsorption of both MB and CV onto the RH was found to be spontaneous and endothermic. This adsorption increased insignificantly on increasing the solution pH from 4 to 10. With an increasing dosage of the RH, there was an increase in the removal percentages of MB and CV; however, adsorption capacity per unit mass of the RH was observed to decrease. Therefore, we conclude that utilizing RH as an available and affordable adsorbent is feasible to remove MB and CV from wastewater.
Keywords: Adsorption; Crystal violet; Methylene blue; Rice husk; Thermal treatment